Hepatic arterial infusion chemotherapy for hepatic cancer end metastases – complications and technical limitations - Szczylik, Cezary; Wcisło, Gabriel; Żołnierek, Jakub; Korniluk, Jan; Brzozowski, Krzysztof; Osiecki, Mirosław; Nurzyński, Paweł; Twarkowski, Paweł; Żukowski, Paweł; Sarosiek, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2003)
The liver is an organ which, due to its specific vascular anatomy, is often the target of the metastatic process of tumors of the gastrointestinal tract. In many cases, liver metastases were detected at the time of the primary gastrointestinal tumor diagnosis; in others just after the surgery; and in still others at a later time. This problem refers to a large number of people both in Poland and elsewhere. The presence of liver metastases is a negative prognostic factor. One of modern therapeutic modalities targeted at liver cancer and metastases is hepatic arterial infusion (HAI). The aim of the procedure is to administer a cytostatic drug through a microcatheter into the hepatic artery which feeds the tumor. The drugs were administered in the form of bolus and included: 5-fluorouracil, cisplatin, carboplatin, epirubicin, irinotecan and gemcitabine. This method is bound to be successful in stopping the development of the disease, and in some cases the liver lesions may regress. The paper describes 249 patients who underwent 1 155 HAI procedures. The analysis focused on technical difficulties and complications following the procedure. Twenty two patients had early complications in the form of bleeding at the site of the puncture, and in three patients intimal detachment occurred. Five patients showed an allergic reaction to the contrast medium. A long-term complication occurred in eight patients. It was a iatrogenic stenosis of the hepatic artery. The biggest technical difficulties during catherisation were caused by advanced atherosclerotic changes in the iliac and visceral arteries. Despite complications and difficulties associated with performing the procedure, it may be considered safe for neoplastic disease patients.